Membangun Kembali Dialog Keagamaan: Telaah Deskriptif-singkat atas Ensiklik Fratelli Tutti Menurut Paus Fransiskus - Fransiskus Sulaiman Otor (Gerakan Indonesia Kita, 2021)
Pope Francis is a pioneer in building religious dialogue in the contemporary era. The Pope recalled the events of the dialogue between Francis Assisi and Sultan Malik Al-Khamil in an atmosphere of brotherhood even in the midst of the Crusades (1219). Exactly 800 years later, he repeated a similar experience. He had a dialogue with Ahmad El-Tayeb, Grand Imam of Al-Azhar in Abu Dhabi (2019). There, the two signed the document “Human Brotherhood for World Peace and Living Together”. A year later, the Pope published the encyclical Fratelli Tutti (2020). Based on the concept of